2005
DOI: 10.1007/bf03016082
|View full text |Cite
|
Sign up to set email alerts
|

Retromolar tracheal tube positioning for patients undergoing faciomaxillary surgery

Abstract: CORRESPONDENCE 341FIGURE Retromolar placement of the tracheal tube with intermaxillary wire fixation in place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2006
2006
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 2 publications
0
14
0
1
Order By: Relevance
“…Successful maxillofacial surgeries have been reported in good number of patients using this technique. [10–12] Tooth loss is not infrequent in Le Fort II fractures and this gap can also be utilized to safely harbor the ETT secured on the maxillary side.…”
Section: Introductionmentioning
confidence: 99%
“…Successful maxillofacial surgeries have been reported in good number of patients using this technique. [10–12] Tooth loss is not infrequent in Le Fort II fractures and this gap can also be utilized to safely harbor the ETT secured on the maxillary side.…”
Section: Introductionmentioning
confidence: 99%
“…A dentist or an oral and maxillofacial surgeon may be the best person to make the decision regarding extraction of the third molar for the sole purpose of creating space for intubation. Dutta et al (2) observed that in adults the retromolar area had enough space for placement of the endotracheal tube in 42 patients undergoing a variety of maxillofacial procedures. However, there is great variation in the retromolar space when third molars are impacted or fully erupted.…”
Section: Discussionmentioning
confidence: 98%
“…Le forte II and III fracture, involving both naso-orbito-ethmoidal complex disruption with occlusal change are ideal cases for this method. 8,9 Its use in craniofacial and orthognathic surgeries was documented by Mertinez-Lage et al 10 The primary indication is space availability in retromolar area, if less then more chances of accidental extubation of ETT.…”
Section: Discussionmentioning
confidence: 99%